Organisational Justice And Affective Commitment: The Mediating Role Of Perceived Organisational Support - Purang, Pooja (Asian Academy of Management (AAM), 2011)
Perception of fairness among employees is a guiding force that influences employee attitude and behaviour. However, the mechanisms associated with justice need to be studied further. This study hypothesises that perceived organisational support (POS) mediates the relationship between organisational justice perceptions and affective commitment of employees. The study was conducted in a multi-national organisation operating in India in the service sector; the sample size was 71 employees. Baron and Kenny's model of studying the mediating relationship was used. The findings showed that POS fully mediates the relationship between distributive justice and affective commitment as well as partially mediates the relationship between procedural justice and affective commitment. This study highlights the importance of fairness and justice in organisations and identifies the mechanism by which employee perceptions of justice influence their loyalty and involvement.